Study on Waste Acid Modificated Industrial Solid Waste Aluminum Ash to Prepare Environmental Functional Materials to Remove Fluoride Ions in Wastewater - Ren, Yuanchuan; Chen, Xiuping; Qu, Guangfei; Wu, Fenghui; Yang, Yuyi; Wang, Zuoliang; Liu, Xinxin; Jin, Caiyue; Hu, Yan (Frontiers in Environmental Science, 2022)
With the rapid development of industry,industrial solid waste has become one of the key concerns in the field of environmental protection. It has the characteristics of huge production and difficulty in resource treatment. At the same time,the waste acid generated by the chemical industry has a greater prospect of resource utilization. In this paper,we studied the preparation of high-performance environmental functional materials as a kind of adsorbent for fluoride removal by using waste oxalic acid and aluminum ash as the main raw materials. The first high temperature combined waste acid modification method was proposed,The adsorption effect of modified adsorbent materials on fluorine under different high temperature calcination conditions was investigated,and the effect of initial concentration,pH,temperature and time on the stable adsorption of fluorine was also investigated. The mechanism of action was analyzed by XRD,SEM,BET and FTIR characterization. The experimental results found that the waste acid-modified calcined aluminum ash had good adsorption effect on fluorine and maintained good stability in the adsorption process. Calcination can increase the adsorption capacity(144.46 mg/g). It is worth mentioning that the modified performance of oxalic acid significantly increased the adsorption capacity to 180.57 mg/g. By studying the adsorption isotherms and kinetics,these adsorption behaviors were found to be consistent with the Freundlich model and the pseudo-secondary model,indicating that chemisorption is the rate-determining step. Acetic acid was used as the regeneration reagent,and the adsorbents obtained all had good recovery performance. The fluoride adsorption process can be attributed to a combination of electrostatic interaction,coordination and ion exchange between M-OH and F-. In addition,the modification of spent oxalic acid exhibits a convenient method to rapidly increase the M-OH content,and this method contributes to the formation of dominant adsorption sites.